2020
DOI: 10.1080/17453674.2020.1807092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on paediatric orthopaedic trauma workload in central London: a multi-centre longitudinal observational study over the “golden weeks”

Abstract: Background and purpose — The COVID-19 pandemic has been recognised as an unprecedented global health crisis. This study assesses the impact on a large acute paediatric hospital service in London, evaluating the trends in the acute paediatric orthopaedic trauma referral caseload and operative casemix before (2019) and during (2020) COVID-19 lockdown. Patients and methods — A longitudinal retrospective observational prevalence study of both acute paediatric orthopaedic trauma referrals and operative c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 18 publications
13
61
0
Order By: Relevance
“…An increase in injuries from RTCs in children was reported by Bram et al in the US (5.2% v 1.8%) 11 and UK by Sugand et al (2% v 1%). 61 Further increases were reported in centres in the US by Lubbe et al (12.9% v 10.9%), 32 and in Italy by Giuntoli et al (21.6% v 19.3%). 30 …”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…An increase in injuries from RTCs in children was reported by Bram et al in the US (5.2% v 1.8%) 11 and UK by Sugand et al (2% v 1%). 61 Further increases were reported in centres in the US by Lubbe et al (12.9% v 10.9%), 32 and in Italy by Giuntoli et al (21.6% v 19.3%). 30 …”
Section: Resultsmentioning
confidence: 83%
“…This was particularly prevalent in the paediatric proportion, as reported by Bram et al (33.7% v 21.7%) 25 and Sugand et al in the UK (6% v 3%). 61 Further increases in falls from height were reported in the spinal department in Italy (55.6% v 16.7%), 22 Australia (12.3% v 11.6%, 0.83) 31 , India (25% v 13.5%), 53 the UK (17.4% v 12.4%). 10 …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Nine studies from eight countries reported a significant reduction in emergency department presentations and operations for injuries among children during government-imposed lockdown restrictions, especially related to admissions and operations for sporting-related injuries and those that occur on playgrounds bans on sports and access to playgrounds [107115]. For example, a study based on data from a large acute paediatric hospital in London, UK, found that the prevalence of referrals for child injuries was reduced by nearly two-thirds during the lockdown from 17 March to 28 April 2020, compared to in the same period in 2019 [111]. In contrast, some centres found a relative increase in injuries, including bicycle injuries [107, 109], burn injuries [116], ingestions and poisonings [108], and electrical injuries [114].…”
Section: Resultsmentioning
confidence: 99%
“…One study reported reduction in paediatric admissions for acute asthma at a London teaching hospital, with suggested reasons including distancing from peers leading to reduced transmissions of respiratory viruses [14]. There are also reports of reduced trauma surgeries as road traffic accidents and sporting injuries were less prevalent during the pandemic [15]. There are concerns that the COVID-19 pandemic will increase levels of antimicrobial resistance in part due to relaxing of antimicrobial stewardship activities [16].…”
Section: Discussionmentioning
confidence: 99%